PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BIMA - Santi, Hanifa Nuri; Yusuf, Muhammad; Darmawan, Imam (Jurnal Nusa Manajemen, 2024)
This research aims to determine the influence of work competency and discipline on employee work performance at the Bima Regency Population and Civil Registration Service. The approach used in the research is an associative approach. The population in the study was 121 people with a sample of 35 ASN people. The data collection techniques used were observation, questionnaires and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, T test and F test which were processed using the Statistical Product and Service Solution (SPSS) version 20 program. that Competency (X1) and Work Discipline (X2) simultaneously have a significant effect on Employee Work Performance at the Population and Civil Registration Service of Bima Regency.